Section Solutions for Chapter 6
Solutions to Exercise 6.1.6
Solutions to Exercise 6.2.6
Inductive step: We begin with the inductive hypothesis. Let \(\displaystyle k\ge 1\) be arbitrary, and suppose that the equality holds for \(\displaystyle n=k\text{;}\) that is, assume that \(\displaystyle b_k=5+4(k-1)\text{.}\)
Now we want to deduce that
Using the recursive relation, we have \(\displaystyle b_{k+1}=b_k+4\) since \(\displaystyle k+1 \ge 2\text{.}\) Using the inductive hypothesis, we have \(\displaystyle b_k=5+4(k-1)\text{.}\) Putting these together gives
as desired. This completes the proof of the inductive step.
By the Principle of Mathematical Induction, \(\displaystyle b_n=5+4(n-1)\) for every \(\displaystyle n \ge 1\text{.}\) ◾Inductive step: We begin with the inductive hypothesis. Let \(\displaystyle k \ge 0\) be arbitrary, and suppose that the inequality holds for \(\displaystyle n=k\text{;}\) that is, assume that \(\displaystyle k! \ge k\text{.}\)
Now we want to deduce that \(\displaystyle (k+1)! \ge k+1\text{.}\) Using the definition of factorial, we have \(\displaystyle (k+1)!=(k+1)k!\) since \(\displaystyle k+1 \ge 0+1=1\text{.}\) Using the inductive hypothesis, we have \(\displaystyle k! \ge k\text{.}\) Putting these together gives
If \(\displaystyle k \ge 1\text{,}\) then
and we are done. If \(\displaystyle k=0\text{,}\) then \(\displaystyle (k+1)!=1!=1 =k+1\) and again the inequality is satisfied. This completes the proof of the inductive step.
By the Principle of Mathematical Induction, \(\displaystyle n! \ge n\) for every \(\displaystyle n \ge 0\text{.}\) ◾Solutions to Exercise 6.3.5
For \(\displaystyle n=12\text{,}\) I can get $12 onto my gift card by buying three increments of $4, since \(\displaystyle 4+4+4=12\text{.}\)
For \(\displaystyle n=13\text{,}\) I can get $13 onto my gift card by buying two increments of $4 and one of $5, since \(\displaystyle 4+4+5=13\text{.}\)
For \(\displaystyle n=14\text{,}\) I can get $14 onto my gift card by buying two increments of $5 and one of $4, since \(\displaystyle 4+5+5=14\text{.}\)
For \(\displaystyle n=15\text{,}\) I can get $15 onto my gift card by buying three increments of $5, since \(\displaystyle 5+5+5=15\text{.}\)
Inductive step: We begin with the (strong) inductive hypothesis. Let \(\displaystyle k \ge 15\) be arbitrary, and assume that for every integer \(\displaystyle i\) with \(\displaystyle k-3 \le i \le k\text{,}\) I can put $\(\displaystyle i\) onto my gift card.
Now I want to deduce that I can put $\(\displaystyle (k+1)\) onto my gift card. Using the inductive hypothesis in the case \(\displaystyle i=k-3\text{,}\) I see that add can put $\(\displaystyle (k-3)\) onto my gift card by buying increments of $4 or $5. Now if I buy one additional increment of $4, I have put a total of $\(\displaystyle (k-3+4)\) = $\(\displaystyle (k+1)\) onto my gift card, as desired. This completes the proof of the inductive step.
By the (strong) Principle of Mathematical Induction, I can put any amount of dollars that is at least $12 onto my gift card. ◾